Engaging the use of information and communication technology (ICT) in promoting a community-based tourism in Sarawak - Connie, Christopher Kesa (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Tourism is a major source of income and also a catalyst for the economic development in Malaysia. Sarawak like other states in Malaysia has realized the importance of tourism contribution to the local economic development and communities. One of the important tourism activities in Sarawak that offers great potentials to generate income to the local communities is home stay program. A home stay program is a community-based tourism initiative and has been identified and prioritized by the state agency as strategic to further progress the tourism sector in Sarawak. In the literature, there has been a lack of research that examines the engagement of ICTs to advance the home stay program in the context of Sarawak. This study aims to address this limitation. This research investigates in what ways ICTs have been engaged in developing and promoting a community-based tourism program and how the home stay operators participate in the process of integrating ICT to enhance this program. More explicitly, this study attempts: (l) to identify initiatives in engaging ICT in developing and promoting a community-based tourism program in the context of Sarawak; (2) to identify factors (perceived benefits, perceived higher cost, ICT knowledge and skills, accessibility to the ICT infrastructure, government support and community support) and determine its relationship with the home stay operators in taking initiative to adopt and use ICT in their context and (3) to provide recommendations to strengthen this business. To obtain data, this study deployed a survey method 102 questionnaires were distributed to selected respondents from seven (7) selected home stay programs in Sarawak namely: Kampung Santubong, Kampung Annah Rais, Kampung Panglima Seman Lama, Kampung Benuk, Kampung Siol Kand.is, Kampung Tebakang Melayu and Kampung Mongkos. Overall, the outcomes of the research reveal that the active home stay operators were mostly female (61.4%) and most of them aged 46 and above (65.7%) years old. Majority of them participate in home stay program as a part-time basis in order to diversify their income. Majority of them earned monthly gross income below RM2000 (60%) however managed to sustain their home stay business more than 5 years (61.45%)~About 64% of the respondents reported below average (i.e. poor or very poor) with regard to ICT skills and knowledge. Due to very poor skills of using ICT, hence it is not surprising that a majority of the respqndents (84.3%) reported that they do not really use ICT to promote their homestay business. Majority of operators (94.5%) at least completed primary school and this explained that they can be trained to improve their ICT skills and knowledge. All selected villages are under Wireless Network Village Program but most of the participants responded that they did not put internet as important medium of communication in their business due to limitation in accessibility of ICT facilities and supporting services. This explained that most of the operators (91.4%) have no knowledge in blogging, 71.4% did no.t used email to communicate in their daily home stay business and 64.3% did not anticipated in the purpose of using ICT in marketing their home stay. The statistical analysis further revealed that five factors (perceived benefits, ICT knowledge and skills, accessibility to ICT infrastructure, government support and community support) have a strong positive and significant relationship whereby perceived higher cost has a strong negative relationship with home stay operators' decision in ICT adoption in the context of Sarawak. ,The outcomes of this study can benefit policy maker and home stay operators.